TEACHING ENGINEERING AND COMPUTER GRAPHICS UNDER THE CONDITIONS OF A CREDIT TRAINING SYSTEM (ResearchJet Journal of Analysis and Inventions, 2021)
This article is devoted to the issues of improving the quality of graphic education based on credit-model teaching technology. The article points out the need to create a model for organizing independent homework of students' graphic work, and also includes recommendations for educational methodological material on the subject of engineering and computer graphics.